2022
DOI: 10.1002/app.53125
|View full text |Cite
|
Sign up to set email alerts
|

3D‐printing carbon nanotubes/Ti3C2Tx/chitosan composites with different arrangement structures based on ball milling for EMI shielding

Abstract: Conductive macroscopic MXene‐based architectures receive tremendous attention for various potential applications. In this paper, the rheology and printing suitability of MXene ink were optimized by ball milling method to ensure good structural integrity and electrical conductivity of the printing structure. Porous CNT/Ti3C2Tx/CS composites were prepared by 3D printing, and the effects of various arrangements on electromagnetic interference shielding (EMI SE) were studied in depth. Since Ti3C2Tx can produce TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…matching layer also increases from 1 to 3 mm, resulting in poor impedance matching and low EMI SE. We summarized the research progress of various EMI shielding materials in the literature, including MXene, CNT, polymer composite membranes/aerogels/frames [16,[51][52][53][54][55][56][57][58][59][60][61][62], and the results are shown in Fig. 5c and Table S3.…”
Section: Tunable Emi Se Performance Of Gcmcp Aerogel Frames With Diff...mentioning
confidence: 99%
“…matching layer also increases from 1 to 3 mm, resulting in poor impedance matching and low EMI SE. We summarized the research progress of various EMI shielding materials in the literature, including MXene, CNT, polymer composite membranes/aerogels/frames [16,[51][52][53][54][55][56][57][58][59][60][61][62], and the results are shown in Fig. 5c and Table S3.…”
Section: Tunable Emi Se Performance Of Gcmcp Aerogel Frames With Diff...mentioning
confidence: 99%
“…(e) Values of EMI SE for the C3P1 composites with a different grid over the X-band frequency range (8.2–12.4 GHz), (f) R and A coefficients of the C3P1 composites with different grids. (g) EMI shielding mechanism (g1: reflection mechanism by electron migration and hopping and multiple internal reflection inside the micropores of the shields; g2: the effect of different grid sizes on the EMI shielding mechanism) and (h) specific EMI shielding effectiveness versus A coefficient for different composites; CNF: cellulose nanofiber, AgNW: silver nanowires, CNT: carbon nanotube, CNC: cellulose nanocrystal, MXene/rGO, Ti 3 C 2 T x -PEDOT:PSS, CNT/Chitosan, TiO 2 –Ti 3 C 2 T x /rGO/PDMS, MXene/CNT/polyimide, PVDF/PEDOT, and ABS/CNT (grid G1:1 mm distance between grids, grid G2:2 mm distance between grids, and grid G3:3 mm distance between grids).…”
Section: Resultsmentioning
confidence: 99%
“…It was known that boron could absorb neutrons [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ]. If a boron-containing coating material has sufficient thickness, most charged neutron particles will be absorbed, and boron-containing materials can prevent neutron migration.…”
Section: Comprehensive Strategies and Solutions To Mitigate And Contr...mentioning
confidence: 99%
“…Generally, membrane shielding materials with porous structures can promote the internal reflection and scattering of electromagnetic waves, and often have better shielding effectiveness than non-porous materials. Pei et al [ 129 ] prepared porous CNT/Ti 3 C 2 T x /CS composites by a combination of ball milling technology and 3D printing technology ( Figure 14 b,c). It was found that CNTs and Ti 3 C 2 T x were uniformly dispersed in the polymer matrix, which is conducive to the construction of a conductive network thus improves the electromagnetic shielding performance of 3D printing devices, which can reach 23.5 dB.…”
Section: Novel Electromagnetic/radiation Shielding Membrane Materials...mentioning
confidence: 99%
See 1 more Smart Citation